From objectivity to subjectivity: Conceptualization and measurement of well-bieng in mental health. (October 2013) - Schrank, Beate; Riches, Simon; Coggins, Tony; Tylee, Andre; Slade, Mike
SUMMARY  The concept of well-being has not been well defined or reliably measured in academic research. This article identifies four academic strands of well-being conceptualization and measurement (economic, medical, psychological and integrative) and shows how well-being has shifted from being conceived as a collectivist concept with objective measures, to being conceived in individualistic terms with subjective measures. Given its clinical relevance the main emphasis is on subjective well-being. While well-being has become a key concept in mental health, the article also discusses some limitations to its use in practice and proposes considerations for future research. Key issues are a consensus definition of well-being in people with mental illness, and empirical studies on the measurement of well-being and its determinants. Future research might be based on the 'good life' approach, the Complete State Model of Mental Health or the academic field of Positive Psychology.